Pagophilus groenlandicus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pagophilus groenlandicus (Erxleben 1777) [Phoca] groenlandica Erxleben 1777, Systema Regni Animalis, Vol. 1: 588. Type Locality: "in Groenlandia et Newfoundland.". Vernacular Names: Harp Seal. Synonyms: Pagophilus albicauda (Desmarest 1822); Pagophilus albini (Alessandrini 1851); Pagophilus dorsata (Pallas 1811); Pagophilus leucopla (Thienemann 1824); Pagophilus oceanica (Lepechin 1778); Pagophilus semilunaris (Boddaert 1785). Distribution: N Atlantic and Arctic oceans and coastal regions of Canada (Newfoundland), France (vagrant), Germany (vagrant), Greenland, Iceland, Norway, Russia from E Canada to the White Sea (Russia), Scotland (vagrant), USA (Virginia - vagrant). Conservation: IUCN – Lower Risk (lc). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 599, DOI: 10.5281/zenodo.7316519